Dissecting JACKDAW transcriptional regulatory module and protein– protein interaction domains - Alidrissi, Louai (KAUST Research Repository, 2019)
Many biological processes are regulated via the action of interacting transcription
factors. Together, these proteins form a complex regulatory network that will lead to
different outcomes according to the DNA context of their target. The transcriptional
regulator JACKDAW (JKD) together with the transcription factors SHR (SHORT-ROOT)
and (SCARECROW) form a regulatory module that control a variety cell type specific
targets to maintain the stem cell niche and regulate asymmetric cell division in the
Arabidopsis root meristem. JKD functions is required to restrict the mobile transcription
factor SHR to a single layer the endodermis by nuclear retention through association
with SCR forming a ternary complex. Unpublished data from a yeast 2 hybrid screen
indicated that JKD forms complexes with other transcriptional regulators involved either
in growth or defense pathways, but the nature and the function of these interactions
are yet to be elucidated. Here we validated these interactions using Yeast 2-Hybrid and
Bimolecular fluorescence complementation (BiFC), which are widely used methods to
study protein-protein interaction and can potentially provide valuable information in
protein-complex composition. We also exploited these two approaches to determine
interaction domains of JKD’s. However, the results from the Y2-H and BiFC assays
showed inconsistent data. This hindered our ability to conclusively define the interacting
JKD variants with various plant-specific transcriptional regulators. As JKD acts as a
transcriptional regulator we tested JKD truncated variants on its target promoter pMYC2
using Dual-luciferase reporter assay in a plant-based expression. Our data indicated the
significance of its ZF1 motif in mediating DNA binding. To assess whether JKD regulates
its targets or in association with SCR and SHR we performed the same assay in a
mammalian-based system to avoid plant transcriptional regulation. Our data indicate
that based on the target DNA sequence, each of these TFs can either act either as an
activator or repressor.